2020
DOI: 10.2147/rmhp.s261093
|View full text |Cite
|
Sign up to set email alerts
|

<p>Relationships Between Eating Behaviors and Hand Grip Strength Among Chinese Adults: A Population-Based Cross-Sectional Study</p>

Abstract: Purpose Poor eating behaviors are associated with imbalances in energy and food intake, which may directly or indirectly contribute to muscle strength loss. This study aimed to investigate the association between eating behaviors and hand grip strength in Chinese adults. Materials and Methods We designed and conducted a cross-sectional study of 2009 Chinese individuals aged 25–65 years in 2017. Eating behaviors, including breakfast consumption, snacking after dinner, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…For the association between breakfast consumption frequency and handgrip strength, three studies reported that regular breakfast consumption is associated with higher handgrip strength level [12,13,14]. Inversely, other three studies did not reveal a signi cant association between them [15,16,17,18].…”
Section: Literature Search and Screeningmentioning
confidence: 99%
See 4 more Smart Citations
“…For the association between breakfast consumption frequency and handgrip strength, three studies reported that regular breakfast consumption is associated with higher handgrip strength level [12,13,14]. Inversely, other three studies did not reveal a signi cant association between them [15,16,17,18].…”
Section: Literature Search and Screeningmentioning
confidence: 99%
“…Finally, only 7 full-text articles met the inclusion criteria and 4 of them were included in meta-analysis. Basic characteristics of the included overall studies Among these 7 studies [12,14,15,16,17,18,21], overall studies design were cross-sectional study examining asosciaiton between breakfast consumption frequency and handgrip strength and reported mean (SD or SE or 95%CI) of handgrip strength for each breakfast consumption frequency category. The studies were conducted in following countries: China (n = 2) [12,21], Japan (n = 1) [14], Korea (n = 1) [16], Ghana (n = 1) [18] and 2 were combined European countries [15,17].…”
Section: Literature Search and Screeningmentioning
confidence: 99%
See 3 more Smart Citations